Finding the spark - Cruz, Gloria (Ready-to-read. Superstar reader!, 2024)
Before they were Megatron and Optimus Prime, these two Transformers were friends stuck working in a mine on Cybertron. But when they meet B-127, he tells the pair that there's a way to get to the surface and escape.